2017
DOI: 10.1063/1.4973716
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high sulfurization temperature drives the growth of oxide-derived Cu2ZnSnS4 thin film with very large grain

Abstract: Small grain size is one of the main obstacles for preparing high efficiency Cu2ZnSnS4 (CZTS) photovoltaic devices. The high thermal energy (high annealing temperature) is used to facilitate the driving force of grain growth. In this paper, the CZTS thin films were synthesized by means of sulfurizing oxide-precursors at relatively high sulfurization temperatures (550–700 °C). The effect of sulfurization temperature on properties of CZTS thin films was investigated through XRD, Raman, SEM, and energy dispersive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, it is observed that the grain sizes reduce at about 580 °C. It can be thought that this could be the result of decomposition of CZTS [31,32]. The film morphology and crystallinity become more uniform and denser between 550-570 °C.…”
Section: The Morphology Of Czts Thin Films On Ti Substratementioning
confidence: 99%
“…However, it is observed that the grain sizes reduce at about 580 °C. It can be thought that this could be the result of decomposition of CZTS [31,32]. The film morphology and crystallinity become more uniform and denser between 550-570 °C.…”
Section: The Morphology Of Czts Thin Films On Ti Substratementioning
confidence: 99%